Specific Inhibition of Soluble γc Receptor Attenuates Collagen-Induced Arthritis by Modulating the Inflammatory T Cell Responses - Lee, Byunghyuk; Jo, Yuna; Kim, Geona; Ali, Laraib Amir; Sohn, Dong Hyun; Lee, Seung-Geun; Kim, Kiseok; Shin, Euisu; Ryu, Sung Ho; Hong, Changwan (Frontiers in Immunology, 2019)
IL-17 produced by Th17 cells has been implicated in the pathogenesis of rheumatoid arthritis (RA). It is important to prevent the differentiation of Th17 cells in RA. Homodimeric soluble γc (sγc) impairs IL-2 signaling and enhances Th17 differentiation. Thus, we aimed to block the functions of sγc by inhibiting the formation of homodimeric sγc. The homodimeric form of sγc was strikingly disturbed by sγc-binding DNA aptamer. Moreover, the aptamer effectively inhibited Th17 cell differentiation and restored IL-2 and IL-15 signaling impaired by sγc with evidences of increased survival of T cells. sγc was highly expressed in SF of RA patients and increased in established CIA mice. The therapeutic effect of PEG-aptamer was tested in CIA model and its treatment alleviated arthritis pathogenesis with impaired differentiation of pathogenic Th17, NKT1, and NKT17 cells in inflamed joint. Homodimeric sγc has pathogenic roles to exacerbate RA progression with differentiation of local Th17, NKT1, and NKT17 cells. Therefore, sγc is suggested as target of a therapeutic strategy for RA.